Agronomic Characterization of the ‘Trompito INTA’ Persian Walnut Cultivar - Carabajal, Dante Edgardo (2022)
‘Trompito INTA’ is a walnut cultivar of Argentine origin, developed at the Catamarca Experimental Station of the Instituto Nacional de Tecnología Agropecuaria (INTA). It was produced in 1984 by controlled pollination between the Persian walnut cultivars ‘Lompoc’ x ‘UC 56–224’. It has a very early to early sprouting and flowering, and it is protandrous with 30–70% overlap between pollen shedding and pistillate flower receptivity. Its harvesting occurs 28 days earlier than that of ‘Chandler’. The tree has weak vigor, semi-upright growth habit, medium density of branches and lateral fructification. The nut is of very large size (37.12 mm), the shell is thin, the kernel color is very light, and kernel percent is very high (> 53.5%). ‘Trompito INTA’ has early harvesting, high-quality nut and kernel attributes and better agronomic performance than ‘Chandler’, mainly at lower elevations. This cultivar is allowing the expansion of the crop in the province of Catamarca, lowering the limit of altitude for walnut cultivation.